1988
DOI: 10.1063/1.99976
|View full text |Cite
|
Sign up to set email alerts
|

Weakly coupled grain model of high-frequency losses in high T c superconducting thin films

Abstract: We propose a model of Josephson coupling between grains to explain the millimeter-wave surface impedance of oriented, polycrystalline thin films of high Tc superconductors. An effective junction IcR product and effective grain size are calculated based on recent measurements of the surface impedance. We suggest a criterion on film quality for the observation of losses intrinsic in the superconductor. The effects of crystalline orientation on surface impedance are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(69 citation statements)
references
References 5 publications
1
67
1
Order By: Relevance
“…The similarity in the frequency dependence of R s would suggest the microwave loss mechanisms at the three dc fields are essentially the same as each others. The linear frequency dependence rules out the loss mechanisms with f 2 dependence, such as two fluid model [25], BCS theory [26] and weakly coupled grain model [1,5]. And it implies that the hysteretic losses due to pinning and nucleation of Josephson fluxons [2] may play an important role in the loss mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity in the frequency dependence of R s would suggest the microwave loss mechanisms at the three dc fields are essentially the same as each others. The linear frequency dependence rules out the loss mechanisms with f 2 dependence, such as two fluid model [25], BCS theory [26] and weakly coupled grain model [1,5]. And it implies that the hysteretic losses due to pinning and nucleation of Josephson fluxons [2] may play an important role in the loss mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…This nonlinearity was believed to be mainly contributed by weak links and vortex dynamics in the HTS films [1][2][3][4][5][6][7][8][9][10][11][12]. Besides, other sources of nonlinearity, such as intrinsic pairbreaking, local heating of grain boundaries and thermal switch of superconducting grains, were also introduced to explain the diverged experimental data [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This residual absorption strongly depends on the quality of the material and is minimal for epitaxiaI c-axis oriented fihns. Recently D. Miller et al [16] demonstrated that the spectral dependence of the residual absorption of a variety of differently prepared YBa2CuaOT-x fihns may be quantitatively described by a model proposed by Hylton et al [10]. The film is treated as network of weakly coupled superconducting grains.…”
Section: Discussionmentioning
confidence: 99%
“…The slow signal is readily identified as a bolometric response by the non -exponential decay which follows from one dimensional heat flow through the substrate to the cold finger [8]. Both types of signals show a nonlinear dependence on intensity which may be explained by the model of an effective resistively shunted Josephson junction which has the properties of a random array of junctions [9,10]. Experimental Bi2Sr2CaCu2Os fihns were was prepared on MgO substrates by excimer laser sputtering and subsequent annealing as described previously [11].…”
Section: Introductionmentioning
confidence: 99%
“…Such data have provided early but strong evidence against the extension to niobium films of weak link models [7][8][9] such as those which describe granular high T c cuprates [18]. Here we concentrate on a set of measurements [12] obtained with krypton as discharge gas and using electropolished copper substrates.…”
Section: Film Residual Resistances: the State Of The Artmentioning
confidence: 99%